A Historical Analysis of the Development of Brunei Darussalam - Suryati Anggraini; Sismalita Sismalita; Lestari Aprilia Sinaga (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze Brunei Darussalam from the perspective of its historical development, government system, and the economic, social, and cultural conditions of its people. This study was conducted to understand the relationship between historical development and the political system and social life in shaping the identity of the modern Brunei nation. The research method used is a qualitative method with a library research approach through data collection from various sources such as books, scientific journals, articles, and relevant documents. The results of the study show that Brunei Darussalam has experienced a long historical development, starting from the Majapahit era to developing into a strong Islamic sultanate. Brunei's government system is an absolute monarchy with the Sultan as head of state, head of government, and religious leader who has significant authority in running the government. The concept of Malay Islam Beraja (MIB) is the main foundation in the government system and state policies. In addition, Brunei's economic condition is supported by petroleum and natural gas resources which have made this country have a high level of prosperity. In their social and cultural life, Bruneian society maintains a Malay identity combined with Islamic values ​​through customs, religious education, the use of the Malay language, and the implementation of Islamic law-based social norms. Thus, history, government system, economic conditions, and socio-cultural life are strongly intertwined in shaping Brunei Darussalam's character as a modern Islamic state.